FLT1 hypermethylation is involved in polycyclic aromatic hydrocarbons-induced cell transformation - He, Zhini; Zhang, Rui; Chen, Shen; Chen, Liping; Li, Huiyao; Ye, Lizhu; Li, Qiong; Wang, Ziwei; Wang, Qing; Duan, Huawei; Niu, Yong; Xiao, Yongmei; et al. (Environmental pollution (1987), 2019)
Coke oven emissions (COEs) are common particle pollutants in occupational environment and the major constituents of COEs are polycyclic aromatic hydrocarbons (PAHs). Previously, we identified aberrant methylation of the fms related tyrosine kinase 1 (FLT1) gene over the course of benzo(a)pyrene (BaP)-induced cell transformation via genome-wide methylation array. To quantify FLT1 methylation, we established a bisulfite pyrosequencing assay and examined the FLT1 hypermethylation in several human cancers. The results revealed that 70.0% (21/30 pairs) of lung cancers harbored hypermethylated FLT1 and concomitant suppression of gene expression compared to the adjacent tissues. This implies that FLT1 hypermethylation might play a role in malignant cell transformation. In addition, FLT1 hypermethylation and gene suppression appeared in primary human lymphocytes in a dose-response manner following COEs treatment. To explore whether FLT1 methylation is correlated with COEs exposure and DNA damage, we recruited 144 male subjects who had been exposed to high levels of COEs and 84 male control subjects. Notably, the FLT1 methylation in peripheral blood lymphocytes (PBLCs) of the COEs-exposed group (19.8 ± 3.2%) was enhanced by 17.9% compared to that of the control group (16.8 ± 2.8%) (P < 0.001). The FLT1 methylation status was positively correlated with urinary 1-hydroxypyrene (1-OHP) levels, an internal exposure marker of PAHs (β = 0.029, 95% CI = 0.010–0.048, P = 0.003) and positively correlated with DNA damage (βOTM = 0.024, 95% CI = 0.007–0.040, P = 0.005; βTail DNA = 0.035, 95% CI = 0.0017–0.054, P < 0.001) indicated by comet assay. Taken together, these findings indicate that FLT1 might be a tumor suppressor, and its hypermethylation might contribute to PAHs-induced carcinogenicity. [Display omitted] •FLT1 hypermethylation might be involved in PAHs-induced cell transformation.•FLT1 hypermethylation is correlated with PAHs-exposed population.•FLT1 hypermethylation might be involved in lung cancer development.